2020
DOI: 10.1093/brain/awz419
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of neurons and astrocytes to TDP-43 proteinopathy in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal and incurable neurodegenerative disease caused by motor neuron loss, resulting in muscle wasting, paralysis and eventual death. A key pathological feature of ALS is cytoplasmically mislocalized and aggregated TDP-43 protein in >95% of cases, which is considered to have prion-like properties. Historical studies have predominantly focused on genetic forms of ALS, which represent ∼10% of cases, leaving the remaining 90% of sporadic ALS relatively understudied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 52 publications
2
62
0
Order By: Relevance
“…This is challenging to study in tissue sections as the arborization of processes is largely lost during sectioning. To address this issue, we used our established directed differentiation protocol to generate highly enriched spinal motor neurons from hiPSCs, which has previously been extensively validated for cellular identity and functionality ( Hall et al , 2017 ), together with its ability to faithfully recapitulate ALS phenotypes ( Luisier et al , 2018 ; Tyzack et al , 2019 ; Smethurst et al , 2020 ).…”
mentioning
confidence: 99%
“…This is challenging to study in tissue sections as the arborization of processes is largely lost during sectioning. To address this issue, we used our established directed differentiation protocol to generate highly enriched spinal motor neurons from hiPSCs, which has previously been extensively validated for cellular identity and functionality ( Hall et al , 2017 ), together with its ability to faithfully recapitulate ALS phenotypes ( Luisier et al , 2018 ; Tyzack et al , 2019 ; Smethurst et al , 2020 ).…”
mentioning
confidence: 99%
“…In contrast, healthy astrocytes protect MNs. Recent study provides evidence for the beneficial role that astrocytes play in protecting MNs in ALS (Smethurst et al, 2020). In this study, the authors first demonstrated that iPSC-derived MNs are more vulnerable to seeded TDP-43 aggregation (extracted from sALS post-mortem spinal-cord) than iPSC-derived astrocytes, indicating a cell-type-specific difference in vulnerability.…”
Section: Role and Therapeutic Potential Of Astrocytes In Alsmentioning
confidence: 80%
“…Intriguingly, the addition of astrocyte-condition-media alone to iPSC-derived MNs, pre-exposed to TDP-43 aggregates, had similar effects on MN. Lastly, the authors demonstrated that highly purified recombinant TDP-43 oligomers reproduced the observed celltype-specific toxicity (Smethurst et al, 2020).…”
Section: Role and Therapeutic Potential Of Astrocytes In Alsmentioning
confidence: 92%
“…Together, these studies demonstrate the power of co-culture for gaining insight into the role of glial cells in the early cellular pathogenesis of AD. Similar effects have been unraveled for a number of neurodegenerative diseases, including ALS [109,117,118], PD [119], and HD [120]. Microglia add an additional dimension to neurodegenerative disease modeling in vitro and can be incorporated into embryoid bodies or other 3D culturing methods to create combined systems.…”
Section: Modeling the Role Of Glia In Neurodegenerative Disease Usingmentioning
confidence: 80%
“…The ALS-associated superoxide dismutase 1 (SOD1) mutation specifically dysregulates the neuroprotective EphB1-ephrin-B1-STAT3 signaling pathway in human iPSC-derived astrocytes, while leaving the IL-6 responsive activity of STAT3 intact. This finding indicates a molecular pathway that imparts increased risk for ALS through an astrocytic cell autonomous mechanism [108,109]. Uncovering molecular mechanisms of disease pathogenesis in glial cells like this both broadens our understanding of the non-cell autonomous contributions to neural degeneration and reveals key glial vulnerable pathways that may be targeted to delay disease onset ( Figure 1C).…”
Section: Modeling the Role Of Glia In Neurodegenerative Disease Usingmentioning
confidence: 91%